Analysis of the Effect of Accounting Information Quality, Institutional Ownership, and Financial Performance on Capital Market Reaction: A Case Study on Company XYZ on the Indonesia Stock Exchange - Fithriah Napu; Ridwansyah Ridwansyah; Sukardi Sukardi; Efendi Sugianto (West Science Accounting and Finance, 2023)
This research investigates the interplay between accounting information quality, institutional ownership, financial performance, and capital market reactions within the context of the Indonesia Stock Exchange (IDX). Employing Structural Equation Modeling with Partial Least Squares (SEM-PLS), a diverse sample of IDX-listed companies spanning various sectors, sizes, and leverage levels was analyzed. The measurement model assessment confirmed the reliability and validity of selected indicators, while the structural model revealed significant positive relationships between accounting information quality and institutional ownership with capital market reactions. Surprisingly, financial performance did not show a direct impact on market reactions. The model exhibited a good fit, explaining 60.2% of the variance in capital market reactions. Implications for investors and corporate decision-makers are discussed, emphasizing the strategic importance of transparent reporting and attracting institutional investors. Limitations include cross-sectional data and potential endogeneity concerns. This research contributes to the understanding of market dynamics in the Indonesian context and suggests avenues for future exploration.